Zoonotic endoparasites and Toxoplasma gondii seropositivity in free-roaming cats (Felis catus) from New York City boroughs - Viet-Linh Nguyen; Elizabeth Gurtowski; Jiayi Chen; Megan Rosen; Pratap Kafle (PLoS ONE, 2026)
Free-roaming cats ( Felis catus ) can serve as reservoirs of various zoonotic parasites in urban settings. Despite a large population of free-roaming cats around New York City, studies assessing the prevalence and shedding of various parasites in the New York urban landscape are scarce. This study utilized fecal and blood samples opportunistically collected during the Trap Neuter Return (TNR) program from 87 free-roaming cats in New York City between May and July 2023. Samples were analyzed using centrifugal fecal flotation, coproantigen immunoassays, serologic assays, and PCR-based assays for gastrointestinal and vector-borne parasites. Fecal flotation (n = 87) results revealed that 57.5% (50/87; 95% CI: 46.9–67.4) of cats were infected with at least one species of parasite. The most prevalent infection was Toxocara spp. (54%; 95% CI: 43.4–64.3), followed by Ancylostoma spp. (13.8%; 95% CI: 8.2–22.6) and coccidia (11.5%; 95% CI: 6.4–19.9). Coproantigen testing (n = 43) identified Giardia spp. in 11.6% (5/43; 95% CI: 5.1–24.5) and Cryptosporidium spp. in 2.3% (1/43; 95% CI: 0.4–12.1) of cats. Antibodies to Toxoplasma gondii were detected in 8.9% (4/45; 95% CI: 3.5–20.7) of serum samples; no Dirofilaria immitis antigen and Cytauxzoon felis DNA were found in the blood samples (n = 45). Male cats were significantly more likely to be infected with Toxocara spp. (OR = 4.36) and, along with juvenile cats (<1 year), shed significantly higher numbers of eggs (p < 0.05), identifying young males as high-intensity “super-shedders” driving environmental contamination. The high prevalence of zoonotic helminths, particularly Toxocara spp., underscores the public health risks associated with unmanaged feline populations in densely populated urban centers. These findings highlight the utility of integrating disease surveillance into TNR programs to monitor urban ecosystem health and mitigate zoonotic risks.